Intertextualidad y androginia en la literatura posmodernista de Lourdes Ortiz: "Eva", "Salome", "La Liberta", "Urraca" y "Aquiles y Pentesilea" - Meagle-Molina, Elizabeth (University of Ottawa (Canada), 2006)
This thesis studies five pieces of Spanish postmodern literature, written by the Spanish author Lourdes Ortiz between 1982 and 2001: two historical novels (Urraca and La liberta), two short stories ("Eva" and "Salome", included in the collection Los motivos de Circe), and a play (Aguiles y Pentesilea ). Departing from the notion "intertextuality" and playing with the concepts of "History" and "Truth", these works establish a dialogue with fundamental canonical texts such as the Old and New Testaments, Platonism, Stoicism, and Greco-Roman Mythology. Based on a "metaphysics of essence", Occidental patriarchy has always counted on some extra-textual entity (i.e. God, the Law) that possesses the power of creation, that is, the Word. This misogynist ideology also believes in words' inherent masculine sexuality/textuality, therefore subjugating "feminine" constructs to an insignificant position under the presupposed "masculine" hegemony. This duality has served to maintain a symbolic order that makes a radical distinction between body/soul, "Other"/"I", a distinction which also refers to the opposition between passive women and active men. In these alienating circumstances, Ortiz's works use an ancient figure and tradition labeled as heresy by hegemonic voices: the myth of the androgyne, whose two components are considered equivalents. It is worth noting that despite all violent attempts to suppress this "undesirable counter-narrative", the encounter and transcendence of opposites embodied in this symbol recurs through History in texts such as the Hebrew myth of Lilith, the first chapter of Genesis, the discourse of Aristophanes in Plato's Symposium, and the alchemical notion of the "Purified Androgyne". Confronting orthodox and ex-centric discourses, the works by Lourdes Ortiz reveal, sometimes ironically, some subtle strategies hegemonic discourses employ to appear as a self-sufficient construction. In order to demystify logocentric Master Narratives and vindicate the anti-essentialist nature of the word, the fictions analyzed empower traditionally silenced female voices (Eva, Salome, Acte, Urraca, Pentesilea). These biblical, historical, and mythological women are considered by Ortiz as doers of their own deeds, women that fight to activate their right to negotiate significant and signifying places within the web of texts all individuals are embedded in.
Keywords: Literature, Modern.; Literature, Romance.